The Spillover Effect of Auditor Sanctions on Corporate Disclosure: Empirical Evidence from Online Interactive Platform in China - Gu, Xiao; Lau, Yeng Wai; Fauzi bin Saidin, Saidatunur (Advances in Social Sciences Research Journal, 2025)
This paper treats auditor sanctions as an exogenous shock and employs a difference-in-differences (DID) model to examine the spillover effects of such sanctions on the information disclosure behavior of client firms. The findings show that, following auditor sanctions, client firms significantly increase the volume of information disclosed on the online interactive platform, indicating that listed companies are responsive to the reputational damage associated with auditor penalties. This result remains robust under a variety of sensitivity checks. Heterogeneity analyses reveal that, from the client firm perspective, the increase in disclosure is more pronounced among non-state-owned enterprises, larger firms, younger listed companies, and those subject to stronger external oversight. From the auditor perspective, clients of harsher sanctioned audit firms exhibit greater increases in disclosure following the sanction. The findings contribute to the literature on the consequences of auditor sanctions and the determinants of corporate disclosure. It also offers practical implications for regulatory authorities seeking to enhance audit enforcement and for firms responding of their auditors’ disciplinary actions.